Patriarchy, Labour Markets and Development: Contesting the Sexual Division of Labour in Sri Lanka. (January 2014) - Withers, Matt; Biyanwila, Janaka
Although certain strides have been made towards increased female participation in paid work, Sri Lanka's labour market remains heavily segmented and offers limited sustainable economic opportunity for a majority of women. Differentiated entitlements determined by gender, ethnicity and class have left women disproportionately burdened by the challenges of economic development. Shaped by neoliberal reforms embedded in patriarchal ethno-nationalist economic policies, women remain over-represented in the labour-intensive, low-paid occupations that have historically formed Sri Lanka's export base and underpinned development. As migrant domestic workers and garment producers, a majority of Sri Lankan women have been restricted to earning their livelihood through vulnerable and exploitative work within stratified labour markets. By framing domestic labour markets as embedded in global production networks, this article explores the potential for International Labour Organization (ILO) and civil society initiatives to shape domestic policy measures to re-regulate labour markets by addressing mechanisms that devalue and marginalize women workers. It then considers the ways in which civil society actors, women workers groups and labour unions contest or complement entrenched patriarchal tendencies within labour markets. Although ILO and state-led measures are significant, the challenges women face in articulating their collective concerns within labour markets remain central to addressing conditions of exploitation that women workers endure.